Ernst Moro: returning the names - I.V. Pashchenko; O.G. Ivanko (Zdorovʹe Rebenka, 2021)
The purpose of the publication is an invitation to honor the outstanding pediatrician Ernst Moro (1874–1951), with an attempt to return his pronunciation of the surname by emphasizing the first syllable (Móro), to recall the life and creative career of this outstanding scientist and doctor. The Moro reflex described in 1918 is now widely used by modern pediatricians and pediatric neurologists in everyday practice. Ernst Moro’s scientific achievements in the development of a skin test for tuberculosis diagnostics, the organization of the efforts against diarrhea in young children, and the formation of pediatric dietology have made Ernst Moro’s scientific heritage extremely important for modern pediatrics.